PRIVACY SHOULDN'T SCARE YOU. - KOBEISSI, NADIM (New Internationalist, 2012)
The article discusses the creation and development of the Instant Messaging application Cryptocat, designed to encrypt messages and increase online security. It addresses increasing interest in and need for computer privacy and security tools, as well as notes opposition to encryption from police and government agencies.